2018
DOI: 10.1021/acs.jpcc.8b07915
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Activation of Graphite Co-intercalation Reactions for Glymes and Crown Ethers in Sodium-Ion Batteries

Abstract: The intercalation of solvated ions into graphite leads to ternary graphite intercalation compounds (t-GICs). Here, we study the impact of temperature on the electrochemical activity of graphite electrodes for co-intercalation reactions between 20 and 80 °C in sodium cells. For this, a range of linear ethers (mono-, di-, tri-, and tetraglyme) are studied. For the first time, pentaglyme and several crown ethers are also investigated. We find that several solvents that appear as unsuitable for the co-intercalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 36 publications
5
47
1
Order By: Relevance
“…The co-intercalation reaction strongly depends on the selection of solvents in the electrolytes because the coordination structures of Na ions are determined by the nature of the cointercalating solvent molecules (Kim et al, 2015a;Jache et al, 2016;Goktas et al, 2018a;Xu et al, 2019). Indeed, the most favorable coordination number of one alkali metal ion in glymebased electrolytes ranges from 4 to 7, leading to complexes with different structures (Matsui and Takeyama, 1998;Rhodes et al, 2002;Henderson, 2006;Kim et al, 2016b).…”
Section: Solvated Alkali and Alkaline Earth Metal-ion Intercalation Imentioning
confidence: 99%
“…The co-intercalation reaction strongly depends on the selection of solvents in the electrolytes because the coordination structures of Na ions are determined by the nature of the cointercalating solvent molecules (Kim et al, 2015a;Jache et al, 2016;Goktas et al, 2018a;Xu et al, 2019). Indeed, the most favorable coordination number of one alkali metal ion in glymebased electrolytes ranges from 4 to 7, leading to complexes with different structures (Matsui and Takeyama, 1998;Rhodes et al, 2002;Henderson, 2006;Kim et al, 2016b).…”
Section: Solvated Alkali and Alkaline Earth Metal-ion Intercalation Imentioning
confidence: 99%
“…Yoon et al 18 and Jung et al 19 described the specific conditions that trigger the co-intercalation reactions in the electrochemical cells based on density functional theory (DFT) calculations. Goktas et al 20 found that several solvents like crown ether that were unsuitable for the co-intercalation reaction at room temperature could be activated at elevated temperatures. It was also unveiled that the co-intercalation in graphite occurs via a fast staging process 21,22 , with the growth of a very thin solid electrolyte interphase (SEI) layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the insertion of sodium into graphite is possible with the addition of a co‐intercalant species: low and well‐defined stage ternary compounds containing sodium can be readily formed, either as an alloy with caesium or potassium, or more often, in solution phase with aprotic solvent molecules . In general, alkali metals dissolved in liquid ammonia generate ternary intercalation compounds with ammonia co‐intercalated between the graphene layers; organic solvent co‐intercalants include THF, 1,2‐dimethoxyethane (DME), alkyl amines, and even crown ethers . Often, a charge transfer agent such as naphthalene or anthracene is added to the reaction to facilitate the intercalation process in organic solvents .…”
Section: Introductionmentioning
confidence: 99%